The Kurds in Erdoğan's Turkey : balancing identity, resistance and citizenship - Gourlay, William (Edinburgh : Edinburgh University Press, 2020)
This book examines the circumstances of the Kurds in 21st century Turkey, under the hegemony of the AKP government. After decades of denial, oppression and conflict, Kurds now assert a more confident presence in Turkey's politics -- but does increasing visibility mean a rejection of Turkey? Recording Kurdish voices from Istanbul and Diyarbakır, Turkey's most important Kurdish-populated cities, this book generates new understandings of Kurdish identity and political aspirations. Highlighting elements of Kurdish identity including Newroz, the Kurdish language, connections to religion, landscape and cross-border ties, it offers a portrait of Kurdish political life in a Turkey increasingly dominated by its president, Recep Tayyip Erdoğan. Within the context of Turkey's troubled trajectory towards democratisation, it documents Kurdish narratives of oppression and resistance, and enquires how Kurds reconcile their distinct ethnic identity and citizenship in modern Turkey.--
Introduction : Eruption in Diyarbakır -- 1. Identity, ethnicity, politics : from Kemalism to 'New Turkey' -- 2. Talking to Kurds about 'identity' -- 3. Demarcating Kurdish culture -- 4. The Kurds and Islam : defying hegemony and the 'caliphate' -- 5. Contesting homeland(s) : city, soil and landscape -- 6. Kurdayetî : Pan-Kurdish sentiment and solidarity -- 7. Oppression, solidarity, resistance -- 8. Kurds as citizens -- Conclusion : Reconciling ethnic identity, citizenship and the 'ideal' in Erdoğan's Turkey?
Includes bibliographical references and index.
William Gourlay is a Teaching Associate at the School of Social Sciences, Monash University. His work has appeared in a number of key journals, including the Journal of Muslim Minority Affairs, Middle East Critique and Ethnopolitics as well as Australian press. This is his first book.
Print version record.
JSTOR
Keywords: Kurds -- Turkey; Kurds -- Turkey -- Ethnic identity; Kurds -- Turkey -- Social conditions; Kurds -- Political activity -- Turkey; Turkey -- Ethnic relations; Turkey -- Politics and government -- 21st century; Asie Mineure -- Relations interethniques; Empire ottoman -- Politique et gouvernement -- 21e siècle.; POLITICAL SCIENCE -- Civics & Citizenship; Ethnic relations; Kurds; Kurds -- Ethnic identity; Kurds -- Political activity; Kurds -- Social conditions; Politics and government; Turkey; 2000-2099; Electronic books; Electronic books